2019
DOI: 10.11152/mu-2051
|View full text |Cite
|
Sign up to set email alerts
|

Value of shear wave elastography for diagnosis of primary prostate cancer: a systematic review and meta-analysis

Abstract: Aim: To evaluate the difference in stiffness between prostate cancer (PCa) and benign tissue based on Young’s modulus determined by shear wave elastography (SWE). In addition, the diagnostic accuracy of SWE for the detection of PCa was evaluated comprehensively.Material and methods: We conducted our systematic review and meta-analysis based on databases of PubMed, Embase and Web of Science. Relevant studies regarding to the diagnostic accuracy of SWE for detecting PCa compared to a reference standard of histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Aging, neoplasia, and metabolic diseases can lead to fibrosis and an increase of tissue stiffness 5 . Thus, tissue stiffness is a clinically relevant parameter for diagnosis and prognosis purposes, as we have here shown that alteration of this mechanical parameter is coupled with the progression of diseases and malignancies associated with kidney cancer and fibrosis 143 , PCa 177 , 178 , bladder cancer 167 , testicular cancer 189 , and infertility related diseases 190 192 . Biochemical, topographical, and mechanical modification of the ECM occurs both at the primary and metastatic site 19 , 21 , 26 , but there is also an important cellular contribution to the altered tissue stiffness by means of cell density, contractility, and traction 82 , 93 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Aging, neoplasia, and metabolic diseases can lead to fibrosis and an increase of tissue stiffness 5 . Thus, tissue stiffness is a clinically relevant parameter for diagnosis and prognosis purposes, as we have here shown that alteration of this mechanical parameter is coupled with the progression of diseases and malignancies associated with kidney cancer and fibrosis 143 , PCa 177 , 178 , bladder cancer 167 , testicular cancer 189 , and infertility related diseases 190 192 . Biochemical, topographical, and mechanical modification of the ECM occurs both at the primary and metastatic site 19 , 21 , 26 , but there is also an important cellular contribution to the altered tissue stiffness by means of cell density, contractility, and traction 82 , 93 .…”
Section: Discussionmentioning
confidence: 81%
“…PCa has a higher cell and vessel density, which is discernibly stiffer than both benign and normal tissues 177 . Given the noninvasive and cost-effective imaging technology of SWE, several studies have been published aiming to evaluate differences in stiffness between PCa and benign tissue based on Young’s modulus 178 (Table 2 ). For all studies discussed here, it was reported that the SWE-obtained Young’s modulus of PCa was significantly higher for benign prostate tissue.…”
Section: Organ-specific Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Correas et al, for example, in a study of 184 patients, established an elasticity threshold of 35-37 kPa [34], unlike Boehm et al which placed the threshold at a higher elasticity value of approximately 50 kPa [46]. However, apart from these differences, high percentages (over 70-80%) have always been found in terms of diagnostic accuracy, sensitivity, specificity, and negative predictive value, which confirmed the correlation between tissue rigidity and malignancy, which was always confirmed by the outcome of the histological examination [47]. In a study of 50 patients undergoing SWE-guided target biopsy on highly suspicious lesions, Ahmad et al report a specificity of 88% and a sensitivity of 90% in patients with PSA less than 20 mg/L and much higher values, both of about 93%, for PSA above 20 mg/L.…”
Section: Shear-wave Elastography (Swe)mentioning
confidence: 87%
“…The most important limitation of 2D-SWE is represented by its low performance in detecting tumors smaller than 5 mm [ 42 ]. Moreover, in order to determine the true sensitivity and specificity of the method, a correlation with histo-pathological sections of radical prostatectomy specimens is finally required [ 43 ]. A further limitation of the technique is represented by the operator subjectivity in detecting prostate areas with high rigidity.…”
Section: Discussionmentioning
confidence: 99%